Sustainability Accounting and Financial Performance of Commercial Banks in Cameroon - Grace Gujung Amoh; Messomo Elle Serge; Samuel Tanjeh Mukah (European Scientific Journal, ESJ, 2025)
This study empirically examined the effect of sustainability accounting on the financial performance of commercial banks in Cameroon from 2018 to 2023. The study focused on how economic, environmental, and social sustainability accounting dimensions influence key financial indicators (Return on Assets and Net Interest Margin). The study employed an ex post facto research design and purposive sampling to select 10 of 19 commercial banks. Purposive sampling was used to select commercial banks that had complete financial statement data for the six (06) years, ranging from 2018 to 2023, consistently filed their annual reports, embraced sustainability accounting in line with global best practice, and integrated sustainability information into their annual reports. Sustainability accounting indicators were obtained from the Global Reporting Initiative. The economic, environmental, and social dimensions were used as independent variables. They were measured using a scoring index derived from previous studies, while Return on Assets and Net Interest Margin served as the financial performance metrics. Data from the selected banks were obtained from secondary sources (Audited financial statements). The analysis involved panel regression and descriptive analyses using E-Views 2025. Results indicated a significant relationship between sustainability accounting dimensions and Return on Assets and Net Interest Margin. The findings suggest that the economic, environmental, and social sustainability accounting dimensions have a notable impact on the Return on Assets and Net Interest Margin of commercial banks in Cameroon. The study recommends that commercial banks in Cameroon should formally integrate economic frameworks into their accounting and reporting systems to monitor their sustainability impact and financial performance continuously.